International Classification of Functioning Disability and Health (ICF) applied on health of hygiene and cleaning worker - Moser, Auristela Duarte (2017)
Introduction. The Technological Revolution brought repercussions on collective and individual aspects in the world of work, however. In Brazil there are still activities characterized by significant physical exhaustion, such as hygiene and cleaning services. Goal.To establish a functionality profile of sanitation workers based on the ICF. Method. Data were collected from an occupational health service and coded based on the CIF. Results. On Body Functions component were identified categories b28010 (pain in the head and neck), b28014 (pain in upper limb), 28013 (back pain), and 28015 (leg pain). On Body Structures component was the highlight for s76002 code (lumbar spine). Were extracted codes relating to the activities and participation, with D2200 (cleaning and disinfection), and d4109 (poor posture), and environmental factors with the e1358 code (chemical risk / sanitizers and disinfectants), and 298 (biological risk) and 2251 (humidity). Conclusion. The Informations subsidized a functional profile that will be used to improve the acquisition of health data by the health team.